Evaluation of physiotherapy for treatment of myofascial pain in dogs with hip dysplasia - Formenton, Maira Rezende (2024)
The objective of the study was to compare two methods of treating pain resulting from trigger points (TPs) in dogs with hip dysplasia. The distribution of TP locations in this animal group was established as a secondary objective. After the selection criteria, 15 animals with 100 TP were allocated into two treatment groups: a group submitted to stretching sessions of the affected muscles (38 TPs), considered as control and standard of treatment. The second group underwent stretching and LASER therapy (LT) application (62 TPs) at a dosage of 5J/cm2 . Both groups underwent four treatment sessions during 15 days, with the evaluator being blind to the groups. As a result, concerning the groups, there was no difference between the groups at the end of the treatment, with both achieving an improvement of more than 30% in pain compared to the initial assessment. There was no gain in analgesia with the addition of LT in the dosage (p=0.4642). The main muscles affected were the longissimus thoracicae, with 73% left side (L) and 83% right side (R), followed by the longissimus lumborum (53%L, 40%R) and quadriceps femoris (47% L and R). Among the main limitations is the subjective nature of pain assessment the principal, which is minimized by prior training and blinding of the evaluator concerning the groups. It is concluded that stretching the muscle groups affected by a TP is a technique that reduces myofascial pain in dogs. However, adding LT at the dose and frequency of application studied did not add analgesia to the treatment. Therefore, future research is recommended with other techniques, such as massage therapy and different dosages of LT, to demonstrate results similar to those obtained in human literature.